: Uso de la realidad virtual en la rehabilitación neuropsicológica del adulto mayor con deterioro cognitivo. - Flores Berrones, Yadira Maribel (2023)
ABSTRACT: The objective of the research was to systematize the use of virtual reality in the neuropsychological rehabilitation of elders with cognitive impairment. The type of research was bibliographic, cross-sectional design with a quantitative approach and a descriptive level. The population was 3,052 scientific articles published from 2013 to 2023, following a non-probabilistic sampling from which 70 bibliographic sources were obtained; The following were analyzed: scientific articles, degree theses, and bibliographic reviews. The databases collected were PubMed, Google Scholar, Elsevier, Scielo, and Redalyc. From the results obtained, it is observed about cognitive deterioration that virtual reality has shown to be a promising tool in the improvement of different cognitive functions such as memory, attention, and spatial perception. One of the most used virtual reality techniques for rehabilitation is the Gradys game, which is used with a frequency of 8 sessions for two weeks with approximately 45 minutes per session, offering users a different and less dangerous way. To perform his rehabilitation, thereby achieving visible improvements in the cognitive functions. Keywords: cognitive impairment, virtual reality, older adults, cognitive functions, neuropsychological rehabilitation.